Evaluación De Métodos Indirectos Para Estimar Biomasa En Un Pastizal Natural Del Sur De Córdoba (Argentina Central) - N., Mónaco; Santa, V.; Rosa, M.J.; Autran, V. (European Scientific Journal, ESJ, 2017)
To optimize grassland management, it is important to evaluate seasonal changes in quality and production according to the characteristics of the environment, allowing planning and rational use of resources. With the objective of finding estimators that fit the actual production of aerial biomass in natural pastures, it was proposed to estimate biomass with the average height of the pasture and by double sampling, by determination by direct weight estimation and by estimation with index assignment. For this purpose, a natural grassland located in the area of influence of the final section of the Chucul River Basin (La Felipa Natural Reserve) was surveyed. Periodically from April 2013 to March 2016, in ten samples taken with 0.25 m2 quadrants, the biomass was cut and weighed, and the height of the present species was measured. In the area surrounding each quadrant, 50 uncorrected visual observations were made by assigning indexes from 1 to 5 and values of estimated weight according to the amount of forage available. Then a correlation analysis was performed and linear regressions were determined between the parameters studied. Real biomass (BR) showed a significant correlation with biomass estimated by Weight (BEP) and biomass estimated by Index (BEI) (p≤0.05).